Regional disparities in the Philippines: structural drivers and policy considerations - Andriesse, Edo (ERDKUNDE, 2017)
This article provides a review of regional inequalities in the Philippines, one of the most challenging countries in Southeast Asia due to its combination of continuing high population growth in both urban and rural areas and lack of gainful employment. The article connects structural drivers of regional disparities to policy options recently proposed in the important book Inequality in Asia and the Pacific, to bring about balanced regional development in Asia by: 1. improving regional connectivity, 2. transferring fiscal resources for greater investment in human capital and better access to public services in poor regions, 3. developing growth poles in lagging regions and 4. reducing barriers to within-country migration. While refinements of current policies and schemes with respect to the first three policy options might lead to curbing the persistence of regional disparities and to faster provincial poverty reduction, promoting more rural–urban migration will likely lead to a relocation of poverty to urban slums; in fact, the poverty incidence in several Philippine core provinces has risen in the last decade. The trends and patterns observed in the Philippines constitute valuable inputs for connecting structural drivers of regional disparities to specific empirical contexts in neighbouring countries and for improving regional policymaking.